Pelapisan Urea dengan Arang Aktif yang Diperkaya Mikroba Indegenus dapat Menurunkan Konsentrasi Endrin - Sri Wahyuni; Indratin Indratin; Widyatmani Sih Dewi; Atmanto Heru Wibowo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2016)
Endrin residues are still remain in the  land field these compounds are no longer used by farmers and have been banned by the government. This residue can stay in the soil longer and persistant. Microbial enrichment is expected to accelerate the degradation of pesticide residues. Microbes stretcher are Bacillus substillis, Heliothrix oregonensis, Catenococcus thiocycli, and Achoromobacter sp obtained from the preliminary research results  from soil isolation of idegenus in LIPI Cibinong Microbiology Laboratory.  Soil for the planting medium obtained from the village of Karawang, Regency Cilamaya Wetan, Cilamaya District. The experiment was conducted in the field by using lysimeter at the Experiment Jakenan station from July 2013 to December 2013. The objective of the was to obtain technology of activated carbon-coated urea and biochar which  enriched microbial indegenus. The experiment was used randomized block design (RCBD) with 3 replications.  Plant used are rice. Insecticide residue analysis was carried out in the laboratory in Bogor Balingtan using gas wchromatography (GC), with the SNI method 06-6991.1-2004. The purpose of this study knowing the capabilities of urea coating with activated carbon enrichment microbia in reducing the concentration of residues endrin. The  objective were urrea coated activated carbon from coconut shell were enriched with microbes on paddy field can lower pesticide residues of endrin until 33.65%.  This carbon as the preferred home. Enrichmentwith microbial indegenuscan improve theeffectivenessof ureacoating biochar andureacoatingactivated carbon coconut shell todecrease concentration of endrin.